(untitled) (GUB Journal of Science and Engineering, 2018)
Knitting is the mostly used fabric manufacturing processes in Bangladesh through which various types of knitted fabrics with different physical and chemical properties are produced. Single jersey derivatives have some dimensional, physical or chemical properties that change according to some factors and processing. These properties also change after dyeing & finishing process. As finishing is mandatory for fabric production, some tests are carried out after finishing stage & proper controlling is done according desired quality. Single jersey fabrics show low strength and higher abrasion resistance than grey fabric after dyeing & finishing. Finished fabric is more stiff than grey. Spirality & shrinkage properties of the single jersey fabric are rapidly change after dyeing & finishing and generally acceptable under the limit. Therefore, this paper is all about the comparison of physical properties among various grey and finished single jersey weft knitted fabrics which will be helpful to know for efficient production, taking corrective actions to minimize changes of basic physical properties and produce quality knit products. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 5(1), Dec 2018 P 6-10